Correction: Contraception use and pregnancy in women receiving a 2-dose Ebola vaccine in Rwanda: A retrospective analysis of UMURINZI vaccination campaign data. - PLOS Medicine Editors (PLoS Medicine)
[This corrects the article DOI: 10.1371/journal.pmed.1004508.].